Pendampingan Penyelenggaraan Pemilihan Kepala Dusun: Transparan dan Akuntabel di Desa Wonokerto Kabupaten Pasuruan - Daryono Daryono; Nunuk Indarti; M. Bayu Firmansyah; Jakaria Umro (Lembaga Pengembangan Kinerja Dosen, 2026)
The Hamlet Head Election is an important part of the practice of village democracy that demands transparent, accountable, and participatory implementation. However, in practice, various obstacles are still encountered, such as limited understanding of regulations by the committee, low democratic literacy of the community, and potential conflicts due to lack of information disclosure. This community service activity aims to accompany the implementation of the Hamlet Head Election in Wonokerto Village so that it runs transparently and accountably. The service methods used include socialization of hamlet head election regulations, technical assistance to the election committee, education to the community regarding the rights and obligations of voters, and monitoring and evaluation of the election implementation. The results of the activity show an increase in the committee's understanding of election procedures in accordance with the principles of village governance, increased community participation, and the implementation of more open and accountable election.Thus, this community service activity can have a positive impact on the implementation of more open and accountable elections, as well as creating a healthy and sustainable democratic climate at the village level.